2020
DOI: 10.1001/jamanetworkopen.2020.25488
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Intensive Lifestyle Intervention in Type 2 Diabetes With Health Care Use, Spending, and Disability

Abstract: IMPORTANCE Intensive lifestyle interventions focused on diet and exercise can reduce weight and improve diabetes management. However, the long-term effects on health care use and spending are unclear, especially for public payers. OBJECTIVE To estimate the association of effective intensive lifestyle intervention for weight loss with long-term health care use and Medicare spending. DESIGN, SETTING, AND PARTICIPANTS This ancillary study used data from the Look AHEAD randomized clinical trial, which randomized p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…For CKD patients, intake can be higher, especially in dialysis patients. The Look AHEAD study showed the benefits of using a reducing diet of 1200–1800 kcal in adult patients with DM2 and GFR < 60 mL/min/1.73 m 2 and albumin/creatinine ratio (ACR) > 30 mg/g [ 82 ].…”
Section: Diet Before and After Bariatric Surgerymentioning
confidence: 99%
“…For CKD patients, intake can be higher, especially in dialysis patients. The Look AHEAD study showed the benefits of using a reducing diet of 1200–1800 kcal in adult patients with DM2 and GFR < 60 mL/min/1.73 m 2 and albumin/creatinine ratio (ACR) > 30 mg/g [ 82 ].…”
Section: Diet Before and After Bariatric Surgerymentioning
confidence: 99%
“…Some studies have suggested that continuous remote evaluation and daily monitoring can effectively refine the management of chronic conditions such as type 2 diabetes mellitus (T2DM), which has a high prevalence and social and economic burden [2,3]. In this sense, digital therapeutics products addressed to patients' individual needs have contributed to ongoing management of daily life habits and to lowering healthcare costs attributed to chronic metabolic diseases [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Multidomain intensive lifestyle intervention (ILI; providing counseling and support for behavioral change and goal setting, healthy diet, and increased physical activity) is recommended for the prevention and management of type 2 diabetes, particularly among persons who have overweight or obesity . Strong evidence suggests that multidomain ILI reduces cardiovascular risk factors among persons with type 2 diabetes across North America, Europe, and Asia, but it is less clear whether ILIs are cost-effective …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Strong evidence suggests that multidomain ILI reduces cardiovascular risk factors among persons with type 2 diabetes across North America, Europe, and Asia, but it is less clear whether ILIs are cost-effective. [5][6][7][8][9] Assessing whether any intervention for type 2 diabetes is worth the cost requires considering the effects on labor productivity. By improving physical function and mental health, lifestyle interventions could have positive effects on labor market participation, productivity at work, and earnings.…”
mentioning
confidence: 99%